2015
DOI: 10.1080/19443994.2014.981928
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of membranes modified by acrylic acid with silver nanoparticles

Abstract: Organic fouling is a very important problem in case of membrane filtration processes. Partially, impact of fouling might be overcome by: back puls, membrane cleaning, cross-flow filtration, or surface modification. In this paper, first, surface modification of membrane by acrylic acid and then silver nanoparticles will be presented. In the first step of modification, acrylic acid is grafted to the surface of the polypropylene capillary membrane, thanks to Fenton-type reaction. Then, membranes are further modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, all these methods are limited to specific membrane materials with functional groups on their surfaces and cannot be applied to other membrane materials. Other studies reported the immobilization of AuNPs with the aid of polyacrylic acid, which was grafted on the membrane surface using gamma-rays [ 28 ], the physisorbed free radical grafting technique [ 29 ], or the Fenton type reaction [ 30 ]. However, the requirements of an inert atmosphere or the introduction of other additional copolymers limits these applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, all these methods are limited to specific membrane materials with functional groups on their surfaces and cannot be applied to other membrane materials. Other studies reported the immobilization of AuNPs with the aid of polyacrylic acid, which was grafted on the membrane surface using gamma-rays [ 28 ], the physisorbed free radical grafting technique [ 29 ], or the Fenton type reaction [ 30 ]. However, the requirements of an inert atmosphere or the introduction of other additional copolymers limits these applications.…”
Section: Introductionmentioning
confidence: 99%
“…The oil-water separation membranes inspired by fish scales have been widely adopted to solve the problem [15][16][17][18] due to its anti-oil properties and underwater superoleophobicity. Nevertheless, the complication of multiplying bacteria on membranes was gradually revealed in recent years [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study shows a simpler unsaturated carboxylic acid (acrylic acid) that works with silver nanoparticles in the process of membrane filtration that avoids nanoparticles to adhere to the surface of the modified membranes, which at the same time show antibacterial/bacteriostatic properties [109]. The main reaction of acrylic acid is polymerization; thus, it is commonly used in the production of plastics, paints, and adhesives.…”
Section: Nanomechanics 144mentioning
confidence: 99%